Strategi pengembangan usaha agroindustri Lidah buaya (Studi Kasus: Usaha Agroindustri Lidah Buaya Duta Purnama di Kelurahan Sidomulyo Barat Kecamatan Tampan Kota Pekanbaru) - Sakinah Rahmadhani; Suardi Tarumun; Eliza ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
The purposes of this research are to analyze net income, efficiency and BEP (Break Even Point) of agro-industrial business of Aloe vera of Duta Purnama and to draft the development strategy that can be applied to this agro-industrial business. The data used in this research are primary data and secondary data. The data analysis method used in this research are basic business analysis by counting the income, profit, efficiency (RCR), BEP unit, BEP income, SWOT analysis and AHP (analytic hierarchy process). Seen from the value of profit, Duta Purnama, the agro-industrial business, has a very promising prospect.  It can be known from the result of the research that the RCR values of Nata De Aloe and Duta Purnama’s cracker business are respectively 1.86 and 1.43. The first main strategy and can be applied to develop the business by using AHP is maintaining the competitive price of products.   Keywords: Income, Efficiency (RCR), Strategy, SWOT Analysis and AHP.